(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article investigates the bioecological characteristics, developmental dynamics, and negative impacts on yield of the walnut moth (Garella musculana Erschoff, 1874), one of the most dangerous pests of walnut (Juglans regia L.) plantations. Based on monitoring conducted under the climatic conditions of the Fergana region, the generations of the pest during the vegetative period and the quantitative damage caused to various plant organs (shoots, leaves, fruits) were analyzed.